2010
DOI: 10.1159/000316346
|View full text |Cite
|
Sign up to set email alerts
|

Important Variations in Parvalbumin Content in Common Fish Species: A Factor Possibly Contributing to Variable Allergenicity

Abstract: Background: Although 95% of fish-allergic patients are sensitized to the major fish allergen parvalbumin, clinical reactions to different fish species vary considerably in symptoms, intensity and frequency in allergic subjects. This study aimed at the quantification of parvalbumin levels in salmon, trout, cod, carp, mackerel, herring, redfish and tuna. Methods: Fish muscle extracts were separated by SDS-PAGE and parvalbumin content was estimated by densitometric band quantification. Individual antisera were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 41 publications
6
112
0
5
Order By: Relevance
“…Teleost fish, including tuna, has two types of muscles: white and dark muscles, and the allergenicity of the muscles mostly depends on the parvalbumin content [5,38]. Parvalbumin, the major and cross-reactive allergen in multiple fish species, is found more abundant in the white than in the dark muscle, and therefore the white muscle is more allergenic [5,35,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teleost fish, including tuna, has two types of muscles: white and dark muscles, and the allergenicity of the muscles mostly depends on the parvalbumin content [5,38]. Parvalbumin, the major and cross-reactive allergen in multiple fish species, is found more abundant in the white than in the dark muscle, and therefore the white muscle is more allergenic [5,35,38].…”
Section: Discussionmentioning
confidence: 99%
“…Parvalbumin, the major and cross-reactive allergen in multiple fish species, is found more abundant in the white than in the dark muscle, and therefore the white muscle is more allergenic [5,35,38]. The parvalbumin content also varies significantly among different fish species [5,38,39], and it was much lower in yellowtail tuna than in other species of fish [5,38]. It was also reported that Gad c 1, Sal s 1, The c 1, herring and wolffish contained the most potent cross-reacting allergens, whereas tuna, together with halibut, flounder, and mackerel, were the least allergenic fish [16].…”
Section: Discussionmentioning
confidence: 99%
“…This verifies that is not only difficult to detect interspecific parvalbumin forms using antibodies, but also intraspecific parvalbumins as they can differ greatly. Detection of fish parvalbumins is further complicated by the impact of food processing such as cooking and canning which may degrade or alter tertiary and quaternary structures of parvalbumin, inhibiting the detection by antibodies (Kuehn et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The fish major allergen, parvalbumin, was quantified for the first time by Lopata et al (2005) in its aerosolized form . Recently, this method was applied for the evaluation of fish allergen levels in foodstuff (Faeste & Plassen, 2008), and for comparing the parvalbumin levels in different species (Kuehn et al, 2010). Commercially, there is only one ELISA kit available for detection of crustacean' allergens in foodstuff: however there is none available for the fish allergens.…”
Section: Detection and Quantification Of Selected Allergens In Seafoodmentioning
confidence: 99%